Fully Abstract Compilation to JavaScript - Fournet, Cédric; Swamy, Nikhil; Chen, Juan; Dagand, Pierre-Evariste; Strub, Pierre-Yves; Livshits, Ben (ACM SIGPLAN-SIGACT Symposium on Principles of Programming Languages (POPL) 2013, 2013)
Many tools allow programmers to develop applications in highlevel languages and deploy them in web browsers via compilation to JavaScript. While practical and widely used, these compilers are ad hoc: no guarantee is provided on their correctness for whole programs, nor their security for programs executed within arbitrary JavaScript contexts. This paper presents a compiler with such guarantees. We compile an ML-like language with higher-order functions and references to JavaScript, while preserving all source program properties. Relying on type-based invariants and applicative bisimilarity, we show full abstraction: two programs are equivalent in all source contexts if and only if their wrapped translations are equivalent in all JavaScript contexts. We evaluate our compiler on sample programs, including a series of secure libraries.